Effect of pine bark (Pinus radiata) extracts on sporulation of coccidian oocysts - Molan, Abdul Lateef; Liu, Zhuojian; De, Shampa (Folia parasitologica, 2009)
A series of experiments have been undertaken to determine the effect of water extracts from pine bark (Pinus radiata) on the inhibition of the sporulation of oocysts of three species of avian coccidia. Tubes containing coccidian oocysts isolated from droppings of coccidia-infected chickens were randomly assigned to 0, 250, 500 and 1000 microg/ml pine bark extract (PBE). The tubes were incubated at 25-29 degrees C for 48 h depending on the species of Eimeria. Sporulation inhibition bioassay was used to evaluate the activity of PBE on the sporulation of coccidian oocysts. The oocysts were gently aerated with an air pump away from sun light. The results show for the first time that water-soluble extracts from pine bark containing 35% condensed tannins have anticoccidial activity as evidenced by their ability to decrease significantly the sporulation of the oocysts of three species of Eimeria, namely Eimeria tenella (Railliet et Lucet, 1891), E. maxima Tyzzer, 1929 and E. acervulina Tyzzer, 1929, under laboratory conditions. Incubation of unsporulated oocysts of these parasites in water containing 500 microg PBE per ml resulted in inhibition of sporulation of these oocysts by about 28-84% relative to the oocysts in the control incubations. In addition, up to 12% of E. maxima oocysts exposed to 500-1000 microg pine bark/ml were containing abnormal sporocysts in terms of size, number and shape.
Keywords: Coccidia; kůra rostlin; rostlinné extrakty; Animals; Plant Extracts; oocysty; Oocysts; zvířata; Plant Bark; borovice; Pinus